Monitoring the impact of COVID-19 in Myanmar: Agricultural input retailers - May 2020 survey round - Goeb, Joseph; Boughton, Duncan; Maredia, Mywish K. (International Food Policy Research Institute, 2020)
Agricultural input retailers play a key role in Myanmar’s agri-food system by supplying farmers with fertilizer, seed, pesticides, and other inputs necessary for successful harvests. Because farm-level input use is an important driver of yields for all major food crops, shocks to the input retail sector have major implications both for rural household welfare and for national food security. COVID-19 and the policies enacted to mitigate its spread have shocked Myanmar’s economy. Agricultural input retailers, like many other businesses, are squeezed between both supply and demand side shocks. On the supply side, agricultural inputs have long, international supply chains that could be disrupted by restrictions on international or internal trade and transport. On the demand side, the shocks to rural households’ incomes, crop prices, and uncertainty could affect input purchases. This research note seeks to help the Ministry of Agriculture, Livestock and Irrigation of the Government of Myanmar and agricultural sector stakeholders understand the related shocks to Myanmar’s agricultural input retailers. We conducted a phone survey with 221 input shop owners and managers to understand (i) the demand-side effects of COVID-19 shocks as reflected in sales of key inputs, such as fertilizers, maize seed, vegetable seeds, and pesticides,the supply-side effects both in general and for key inputs, and (iii) business responses to COVID-19 shocks.